Graphene: Hexagonal Boron Nitride Composite Films with Low-Resistance for Flexible Electronics - Irina V. Antonova; Marina B. Shavelkina; Artem I. Ivanov; Dmitriy A. Poteryaev; Nadezhda A. Nebogatikova; Anna A. Buzmakova; Regina A. Soots; Vladimir A. Katarzhis (Nanomaterials, 2022)
The structure and electric properties of hexagonal boron nitride (h-BN):graphene composite with additives of the conductive polymer PEDOT:PSS and ethylene glycol were examined. The graphene and h-BN flakes synthesized in plasma with nanometer sizes were used for experiments. It was found that the addition of more than 10−3 mass% of PEDOT:PSS to the graphene suspension or h-BN:graphene composite in combination with ethylene glycol leads to a strong decrease (4–5 orders of magnitude, in our case) in the resistance of the films created from these suspensions. This is caused by an increase in the conductivity of PEDOT:PSS due to the interaction with ethylene glycol and synergetic effect on the composite properties of h-BN:graphene films. The addition of PEDOT:PSS to the h-BN:graphene composite leads to the correction of the bonds between nanoparticles and a weak change in the resistance under the tensile strain caused by the sample bending. A more pronounced flexibility of the composite films with tree components is demonstrated. The self-organization effects for graphene flakes and polar h-BN flakes lead to the formation of micrometer sized plates in drops and uniform-in-size nanoparticles in inks. The ratio of the components in the composite was found for the observed strong hysteresis and a negative differential resistance. Generally, PEDOT:PSS and ethylene glycol composite films are promising for their application as electrodes or active elements for logic and signal processing.